Pengaruh Penerapan Gaya Mengajar Komando Terhadap Gerak Dasar Dalam Menggiring Bola Dengan Punggung Kaki Pada Permainan Sepak Bola Siswa SMP Kristen Senduk - Yuliana Sattu; Edita Pinangkaan; Abrindo Sumendap (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
The main concern addressed in this research is whether implementing a directive teaching approach influences the enhancement of fundamental dribbling skills using the back foot in soccer among students at Senduk Christian Junior High School. The study employed an experimental design, dividing 20 participants into two groups of 10 each, and utilized a randomized controlled pre-test and post-test design. The assessment tool employed evaluated the proficiency in basic dribbling techniques using the top of the foot during soccer matches. The hypothesis posited that employing a directive teaching style would impact the learning of fundamental dribbling techniques using the sole of the foot in soccer among students at Senduk Christian Junior High School. Data analysis involved the use of the t-test, preceded by tests for data variance homogeneity and normality. The hypothesis suggested that employing a directive teaching style influences the acquisition of basic dribbling skills among Senduk Christian Junior High School students. The study concluded that utilizing a directive teaching style indeed contributes to the improvement of basic dribbling skills using the sole of the foot in soccer matches among students at Senduk Christian Junior High School. This was supported by a calculated t-value exceeding the critical t-value, where t-value = 4.891 > critical t-value = 2.101.